Dark-Field Imaging on a Clinical CT System: Modelling of Interferometer Vibrations - Schmid, Clemens; Viermetz, Manuel; Gustschin, Nikolai; Haeusele, Jakob; Lasser, Tobias; Koehler, Thomas; Pfeiffer, Franz (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
X-ray computed tomography (CT) is an invaluable imaging technique for non-invasive medical diagnosis. However, for soft tissue in the human body the inherent small difference in attenuation limits its significance. Grating-based X-ray phase-contrast is a relatively novel imaging method which detects additional interaction mechanisms between photons and matter, namely refraction and small-angle scattering, to generate additional images with different contrast. The experimental setup involves a Talbot-Lau interferometer whose susceptibility to mechanical vibrations hindered acquisition schemes suitable for clinical routine in the past. We present a processing pipeline to identify spatially and temporally variable fluctuations occurring in the first interferometer installed on a continuously rotating clinical CT gantry. The correlations of the vibrations in the modular grating setup are exploited to identify a small number of relevant vibration modes, allowing for an artifact-free reconstruction of a sample.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed Tomography; Factor Analysis; Grating-based X-ray differential phase contrast; Medical Imaging; Phase Retrieval